The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jop.12765
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IL‐6 expression in human salivary gland cell line by IL‐17 via activation of p38 MAPK, ERK, PI3K/Akt, and NF‐κB pathways

Abstract: The HSG cells expressed IL-17R and reacted to IL-17 to generate IL-6 via the stimulation of ERK, p38 MAPK, Akt, and NF-κB signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The concentration of these cytokines was 47,508.89 pg/ml, 23,869.67 pg/ml, 22,592.24 pg/ml, and 11,697.53 pg/ml, respectively. We also found that uPAR [3538], IL-6 [39], osteopontin (OPN) [4042], Angiopoietin-2 (ANG-2) [43], HGF [4446], TGFb1 [47, 48], RBP4 [49], Angiopoietin-1 (ANG-1) [5052], FAP [53], IL-11 [54, 55], Follistatin [56], DcR3 [57], Galectin-1 [58], MIF [59, 60], IGF-2 [61, 62], MCP-1 [63], and IL-8 [64, 65] were moderately secreted by hAMSCs, which may activate AKT signaling (Fig. 8a, b).
Fig.
…”
Section: Resultsmentioning
confidence: 74%
“…The concentration of these cytokines was 47,508.89 pg/ml, 23,869.67 pg/ml, 22,592.24 pg/ml, and 11,697.53 pg/ml, respectively. We also found that uPAR [3538], IL-6 [39], osteopontin (OPN) [4042], Angiopoietin-2 (ANG-2) [43], HGF [4446], TGFb1 [47, 48], RBP4 [49], Angiopoietin-1 (ANG-1) [5052], FAP [53], IL-11 [54, 55], Follistatin [56], DcR3 [57], Galectin-1 [58], MIF [59, 60], IGF-2 [61, 62], MCP-1 [63], and IL-8 [64, 65] were moderately secreted by hAMSCs, which may activate AKT signaling (Fig. 8a, b).
Fig.
…”
Section: Resultsmentioning
confidence: 74%
“…Th17 and Treg cells play important roles in regulating NLRP3 inflammasome. The imbalance of Th17/Treg has been reported to trigger NLRP3 inflammasome activation through the IL-17/NF-κB pathway ( Wei et al, 2018 ; Yang et al, 2018 ). Therefore, we focused on the role of the NLRP3 inflammasome in the present study and found that EAT rats displayed increased NLRP3 immunostaining signal and protein expressions of NLRP3, ASC, cleaved-Caspase1, cleaved-IL-1β, and IL-18 in the thyroid, suggesting the activation of NLRP3 inflammation following EAT challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PLC/PKC are related to the activation of MAPK and NF- κ B, and the phosphorylation of Gab2 can promote the expression of the PI3K/Akt pathway [37, 38]. The activation of MAPK and PI3K/Akt signaling pathways can induce the expression of inflammatory cytokines and degranulation in the mast cells [39]. The results showed that IMP decreased the expression levels of Akt and MAPK, in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%